PRINCIPAL'S STRATEGY FORMULATION IN IMPROVING STUDENT ACHIEVEMENT - Chotimah, Chusnul; Manusr, Ali (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
This research aims to find out how principals formulate strategies to improve student achievement. This research used a qualitative approach, seeking to explore the vision and mission, environmental analysis and selection of strategies implemented by Principals. Data were collected using participant observation at MA NU Mojosari Nganjuk as well as interviews with the head of the madrasa and deputy head of the madrasa at the institution. This study produced three main findings: First, the vision and mission implemented by principal in achieving academic and non-academic achievements must be formulated clearly, comprehensively and specifically mentioning achievement. Second, there are two parts to the environmental analysis carried out to improve achievement, namely internal and external analysis. Internal analysis covers the weaknesses and strengths of the institution, while external analysis covers opportunities and threats. Third, strategy selection is carried out based on environmental analysis. The chosen strategy must lead to increased academic and non-academic achievement.